Analisis Tindak Tutur Lokusi dalam Video Pembelajaran Bahasa Indonesia pada Kanal YouTube Arisa Nur Aini - Dita Idmania; Andini Bella Pertiwi; Rizki Ayudika Yulistiani; Rizkamalia Ciptarini Mega Gustami; Salsabila Zain Syafa; Asep Purwo Yudhi Utomo; Dyah Prabaningrum; Ferani Mulianingsih (STIKes Ibnu Sina Ajibarang, 2025)
Language serves as a fundamental tool for human communication. On social media platforms like YouTube, various forms of expression utilize both direct and indirect language. Language acts as a symbol shaped by human experiences that are intrinsically linked to behavior and action. This concept illustrates that everything in the human mind can be expressed through written and spoken words. This research adopts a descriptive qualitative approach, employing the